Comparison of Online Sexual Activity Among Iranian Individuals With and Without Substance Use Disorder: A Case-Control Study - Soraya, Shiva; Rashedi, Vahid; Saeidi, Mahdieh; Hashemi, Pooria; Hadi, Fatemeh; Ahmadkhaniha, Hamidreza; Shalbafan, Mohammadreza (Frontiers in Psychiatry, 2022)
The most important practical concerns in addiction medicine are the non-substance addiction and related behaviors among people with substance use disorder. On the other hand, technological advances and easy access have increased the frequency of online sexual activities (OSAs) as one of these behaviors. This study aimed to compare the prevalence of OSAs, based on the Internet Sex Screening Test (ISST) scores, among 60 people with substance use disorder referred to Iran Psychiatric Hospital and 60 non-dependent individuals. The results showed significant negative correlations between the ISST scores and age, age at the onset of substance use, and substance use duration. There was a significant difference between the ISST scores of the case and control groups (P = 0.001(. People who start using substances at an early age and have a long history of substance use are more likely to engage in other addictive behaviors such as OSAs. Therefore, it is critical to consider OSAs and other addictive behaviors in patients with substance use disorder to provide better care for this vulnerable community.